2019
DOI: 10.1007/s10461-019-02507-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Social Marketing Interventions to Improve HIV Testing Among Gay, Bisexual and Other Men Who Have Sex with Men: A Systematic Review

Abstract: HIV testing is central to biomedical HIV prevention, but testing among men who have sex with men remains suboptimal. We evaluated effectiveness of mass media and communication interventions to increase HIV testing and explored patterns between study type, internal validity and intervention effectiveness for the first time. Five databases were searched for articles published between 2009 and 2016 using standard MeSH terms. Eligible studies were quality appraised using standard checklists for risk of bias. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…The current paper is part of a series of papers presenting findings from a systematic review exploring evidence related to mass media and communication interventions to increase HIV testing among GBMSM. More detailed analysis relating to intervention effectiveness (McDaid et al, 2019), the active content of interventions (Flowers et al, 2019) and affect used within interventions (Langdridge et al, 2020) can be found elsewhere. The current analyses employed rigorous data extraction tools to attempt to identify the common social marketing principles and visual design elements associated with effectiveness across a range of HIV testing campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…The current paper is part of a series of papers presenting findings from a systematic review exploring evidence related to mass media and communication interventions to increase HIV testing among GBMSM. More detailed analysis relating to intervention effectiveness (McDaid et al, 2019), the active content of interventions (Flowers et al, 2019) and affect used within interventions (Langdridge et al, 2020) can be found elsewhere. The current analyses employed rigorous data extraction tools to attempt to identify the common social marketing principles and visual design elements associated with effectiveness across a range of HIV testing campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the systematic review are reported in McDaid et al . (); however, we have included a summary of the procedure undertaken for the review to provide a background to the current analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Five electronic databases (CINAHL, Embase, Medline, PsycInfo, and Web of Science) were searched for studies published since 2009, using detailed search strategies and standard MESH terms for HIV, MSM, and mass media interventions (for details of an example search strategy see McDaid et al, 2019). In addition to database searches, reference lists of included articles were searched manually.…”
Section: Search Strategymentioning
confidence: 99%
“…Previous studies have investigated strategies such as social media,5 partner notification6 or social marketing campaigns7 to deliver HIV interventions among high-risk populations. However, these interventions alone are not sufficient because they neglect the importance of the construction and characteristics of the interpersonal social network that are closely associated with HIV transmission 8.…”
Section: Introductionmentioning
confidence: 99%